Utilization of Corn Cob (Zea mays L.) as Raw Material Eco-Friendly Bioethanol - Husainah Yusuf; Muhammad Ridhwan; Azwir; Almukarramah; Erdi Surya (Postgraduate, University of Mataram, 2026)
The use of agricultural waste as an alternative energy source represents a strategic solution to address energy crises and environmental challenges. Corn cobs (Zea mays L.), often regarded as low-value agricultural residues, possess significant potential as a bioethanol feedstock due to their high lignocellulosic content. This study aims to analyze the potential of corn cobs as a raw material for environmentally friendly bioethanol production through hydrolysis and fermentation processes. The research employed an experimental approach consisting of material pretreatment, lignocellulosic hydrolysis to convert cellulose and hemicellulose into fermentable sugars, and fermentation using Saccharomyces cerevisiae as the bioethanol-producing microorganism. Bioethanol yield and production efficiency were evaluated to determine feasibility and performance. The findings indicate that corn cobs can produce bioethanol in competitive yields compared with other lignocellulosic feedstocks. The hydrolysis process effectively increased reducing sugar content, supporting optimal fermentation performance. In addition to technical feasibility, the utilization of corn cobs offers ecological advantages, including the reduction of agricultural waste accumulation and lower carbon emissions. Since corn cobs do not compete with food resources, their use aligns with renewable energy development strategies and circular economy principles. Corn cobs demonstrate strong potential as a sustainable and environmentally friendly bioethanol feedstock. Optimizing production efficiency at an industrial scale and strengthening policy support are recommended to enhance the development and commercialization of agricultural waste-based bioenergy.